(untitled) (Medical Forum Monthly, 2024)
Objective: The current study is to evaluate the gender differences in the prevalence of dental caries.. Study Design: It is an observational cross sectional study. Place and Duration of Study: This study was conducted at the undergraduate level dental students at Islam Dental College, Sialkot from May, 2017 to January, 2018. Materials and Methods: A sample of 156 undergraduate dental students was selected representing both genders with age 18-25 years. The The Decayed, Missing, Filled (DMF) index (DMFT index) was used to quantify the aggregate life of the dental caries. The students were demanded to sit upright on the dental chair. Sterilized instruments were used for each student separate. World Health Organization (WHO) recommended procedure was followed to examine the oral dental status regarding caries. All permanent teeth were examined for the presence of caries. The relationship between gender and the prevalence of dental caries was assessed by the Chi-square test. Independent t-test was performed to test means differences between groups. P-value ≤ 0.05 was considered as significance results. Results: A sample of 156 students was examined. The results of this study revealed that average overall DMFT score difference was not found significant with gender (1.64±1.25 vs 1.40±1.16; p=0.282). However, number of dental caries that is the factor of DMFT average was statistically significant with p=0.002 and number of missing teeth was significant (p=0.045) with graduate study years. Conclusion: Females were the most affected by dental caries. According to DMFT scale low level decayed was presented in undergrad dental students. Relationship between DMFT score and age groups was highly statistical significant. However, the decayed factor of the average DMFT score was significant while other factors of DMFT score were non-significant.